A Study on Endemic Fluorosis in Domestic Ruminants - kumar, Sandeep; Verma, Yamini; Swami, Madhu; Baghel, RPs (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
An epidemiological study was conducted to assess the toxic effect of fluoride in domestic ruminants in the fluoride polluted localities of Seoni district of Madhya Pradesh, India. Sixty animals (20 buffaloes, 20 cattle, and 20 goats) were included in the study in the areas having about 5.0-6.2 ppm fluoride level in drinking water. Dental lesions (clinical score 0 to 5) were the most common clinical signs, followed by bony exostosis and lameness in affected animals. The other signs like emaciation, hoof deformity, hypogalactia, anestrous and repeat breeding were reported by farmers in the animals of fluoride polluted area. High fluoride concentrations were observed in serum samples of buffalo, cattle and goats (0.380±0.022, 0.233±0.022 and 0.181± 0.011 µg/ml) as compared to their respective controls. Haematological parameters in naturally fluoride toxicated animals revealed significant reduction in haemoglobin concentration, packed cell volume, total erythrocyte count and leukocyte count indicative of anemia due to fluoride stress. The differential leukocyte count revealed significantly higher lymphocytes per cent and lower neutrophils per cent in animals of fluoride polluted area as compared to unpolluted area.